The effect of trait anxiety on success in individual athletes - Ahmet Sanıoglu; Mihriban Ulker; Zehranur Sanıoglu Tanıs (Selcuk University, 2017)
Many athletes are not able to show their performances in their training sessions under stressful competition conditions. One of the important reasons for this problem is the anxiety level of the athletes. But anxiety can be a necessary function for success as well as an athlete's ability to make a right decision by making the right decisions. When the athlete is in anxiety, he or she will be better motivated and better able to succeed. With all this, the aim of this study is to determine the effect of success on individual sports. For this purpose, a questionnaire was applied to a total of 407 individual sportsmen in Konya. According to the results of the research, a statistically significant difference was found between the trait anxiety scores of the subjects participating in the research according to the sports branches.